(untitled) (Research, Society and Development, 2024)
The objective of this article is to highlight the main functions of the pharmacist in community pharmacies and the barriers encountered in carrying out the activities necessary to dispense medicines in a safe and effective manner. The present study followed the Literature Review methodology, of an integrative type and with a qualitative approach, the following databases were used: Scielo, Lilacs and Medline. The evolution of community pharmacy took place in relation to how it came to be seen, nowadays this establishment has become of great importance combined with the actions of the pharmacist to dispense medicines in a safe and effective way, reducing self-medication rates and improving each time more information to the population about their disease and its pharmacological treatment. But to do this, the pharmacist needs to have specific knowledge to always improve the safety of individual instructions carried out in the community pharmacy and thus contribute to improving the patient’s quality of life.